Analysis of The Efficiency Level of Zakat Management Institutions in Indonesia: Data Envelopment Analysis (DEA) - Moch. Adi Nur Ikhsan; Muzakar Isa; Muhammad Sholahuddin; Edy Purwo Saputro (LP2M IAIN Palopo, 2025)
Zakat management in Indonesia faces significant challenges in achieving efficiency, even though the potential for national zakat is very large per year. The actual collection, which remains below 10% of this potential, indicates that the performance of zakat management institutions both governmental and non-governmental has yet to be optimized. This study aims to measure the efficiency levels of zakat management institutions in Indonesia, identify the factors that influence their efficiency, and analyze the differences in efficiency based on institutional clusters: government, civil society organizations, and corporate-based institutions. A quantitative descriptive approach was employed using Data Envelopment Analysis (DEA) applied to the audited financial reports of 14 zakat institutions over the period 2019–2023. Input variables included total operational costs, personnel expenses, and total assets, while output variables consisted of the amount of zakat collected and distributed. The findings reveal that not all institutions operate at optimal technical efficiency. Zakat institutions managed by civil society organizations demonstrated the highest efficiency, followed by corporate-based institutions, with government institutions showing the lowest levels of efficiency. The variation in efficiency across clusters is attributed to differences in organizational structure, decision-making flexibility, technological adoption, and community engagement. This study provide critical implications for improving zakat governance and offer strategic insights for policymakers and zakat managers to enhance institutional efficiency and maximize the potential of zakat funds in Indonesia.